2022
DOI: 10.1038/s41467-022-31133-6
|View full text |Cite
|
Sign up to set email alerts
|

Phasing analysis of lung cancer genomes using a long read sequencer

Abstract: Chromosomal backgrounds of cancerous mutations still remain elusive. Here, we conduct the phasing analysis of non-small cell lung cancer specimens of 20 Japanese patients. By the combinatory use of short and long read sequencing data, we obtain long phased blocks of 834 kb in N50 length with >99% concordance rate. By analyzing the obtained phasing information, we reveal that several cancer genomes harbor regions in which mutations are unevenly distributed to either of two haplotypes. Large-scale chromosomal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 85 publications
1
7
0
Order By: Relevance
“…Importantly, we found that EGFR pathway inhibitors were possibly beneficial for the treatment of tumors with a high CHP score. Seemingly consistent with this finding, chromothripsis is frequently detected in lung cancers driven by EGFR mutations ( 28 ), and mutation of EGFR and ERBB2 is associated with more rearrangement events in LUADs ( 29 ). A correlation between EGFR amplification and chromothripsis has also been detected in glioblastoma ( 30 ).…”
Section: Discussionsupporting
confidence: 68%
“…Importantly, we found that EGFR pathway inhibitors were possibly beneficial for the treatment of tumors with a high CHP score. Seemingly consistent with this finding, chromothripsis is frequently detected in lung cancers driven by EGFR mutations ( 28 ), and mutation of EGFR and ERBB2 is associated with more rearrangement events in LUADs ( 29 ). A correlation between EGFR amplification and chromothripsis has also been detected in glioblastoma ( 30 ).…”
Section: Discussionsupporting
confidence: 68%
“…However, after the initial report of the human genome and methylome by nanopore sequencing in 2018 and 2017, respectively 10 , 11 , the potential of long-read sequencing in cancer genomics and epigenomics has been only preliminarily explored. Long-reads analyses have clearly shown higher accuracy and sensitivity to detect SVs in the DNA or plasma of a few breast-cancer 12 and lung-carcinoma samples 13 . As well, informative DNA methylation profiles have been obtained in breast cancer cell lines 10 and series of hepatocellular carcinoma 14 and brain-tumor 15 samples.…”
Section: Introductionmentioning
confidence: 99%
“…An analysis of the genetic makeup of 20 patients with NSCLC revealed the presence of chromothripsis regions, where an abnormal accumulation of single nucleotide variations (SNVs) and structural variations (SVs) were observed on a particular haplotype [ 110 ]. Additionally, it is believed that a number of lung cancer driver fusion oncogenes result from chromothripsis [ 111 ].…”
Section: Intratumoral Heterogeneitymentioning
confidence: 99%